2004
DOI: 10.17221/3423-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Esters of 3-chloropropane-1,2-diol in foodstuffs

Abstract: S��������� B., N������ O., D������� V., R������ Z., D������ M., V������ J. (2004): Esters of 3-chloropropane-1,2-diol in foodstuffs. Czech J. Food Sci., We provide here for the first time the evidence that 3-chloropropane-1,2-diol (3-MCPD) occurs in foodstuffs in its free form and also in the form of esters with higher fatty acids. These esters represent a new class of food contaminants as 3-MCPD may be released in vivo by a lipase-catalysed hydrolysis reaction. We analysed 20 samples of selected retail food p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
86
1
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(97 citation statements)
references
References 15 publications
1
86
1
9
Order By: Relevance
“…A very high concentration of bound 3-CPD in French fries (6100 µg/kg) was reported by Svejkovská et al (2004), while Zelinková et al (2009b) found bound 3-CPD concentrations at the level of 100-258 µg/kg and Hamlet and Asuncion (2009) found concentrations of 35-397 µg/kg. The content of bound 3-CPD in crisps was 48-1186 µg/kg (Hamlet & Asuncion 2009) and 229-1008 µg/kg (Zelinková et al 2009b), respectively.…”
mentioning
confidence: 84%
“…A very high concentration of bound 3-CPD in French fries (6100 µg/kg) was reported by Svejkovská et al (2004), while Zelinková et al (2009b) found bound 3-CPD concentrations at the level of 100-258 µg/kg and Hamlet and Asuncion (2009) found concentrations of 35-397 µg/kg. The content of bound 3-CPD in crisps was 48-1186 µg/kg (Hamlet & Asuncion 2009) and 229-1008 µg/kg (Zelinková et al 2009b), respectively.…”
mentioning
confidence: 84%
“…w postaci mono-lub diestrów kwasów tłuszczowych. Podawane są przykłady żywno-ści, w której estry 3-MCPD z kwasami tłuszczowymi występują w stężeniu kilku lub nawet kilkuset razy większym niż wolny 3-MCPD [70]. Wprowadzono termin "chloropropanodiole związane" [70], np.…”
Section: Estry Chloropropanoli I Chloropropanodioliunclassified
“…Podawane są przykłady żywno-ści, w której estry 3-MCPD z kwasami tłuszczowymi występują w stężeniu kilku lub nawet kilkuset razy większym niż wolny 3-MCPD [70]. Wprowadzono termin "chloropropanodiole związane" [70], np. 3-MCPD związany, oznaczany jako 3-MCPD-E (E -od ester) czy 3-MCPD-PP lub 3-MCPD-O, co oznacza odpowiednio: dipalmitynian lub oleinian 3-MCPD.…”
Section: Estry Chloropropanoli I Chloropropanodioliunclassified
“…Codex established the maximum level of 3-MCPD in liquid seasonings containing acid-HVP based on an international risk evaluation 2 . In the 1980s, 3-MCPD fatty acid esters 3-MCPD-Es were found in trace amounts in heat-processed foods 3,4 .…”
Section: Introductionmentioning
confidence: 99%